The Corticostriatal System in Dissociated Cell Culture - Randall, Fiona E.; Garcia-Munoz, Marianela; Vickers, Catherine; Schock, Sarah C.; Staines, William A.; Arbuthnott, Gordon W. (Frontiers in Systems Neuroscience, 2011)
The sparse connectivity within the striatum in vivo makes the investigation of individual corticostriatal synapses very difficult. Most studies of the corticostriatal input have been done using electrical stimulation under conditions under which it is hard to identify the precise origin of the cortical input. We have employed an in vitro dissociated cell culture system that allows the identification of individual corticostriatal pairs and have been developing methods to study individual cortical neuron inputs to striatal neurons. In mixed corticostriatal cultures, neurons had resting activity similar to the system in vivo. Up/down states were obvious and seemed to encompass the entire culture. Mixed cultures of cortical neurons from transgenic mice expressing green fluorescent protein (GFP) with striatal neurons from wild-type mice of the same developmental stage allowed visual identification of individual candidate corticostriatal pairs. Recordings were performed between 12 and 37 days in vitro (DIV). To investigate synaptic connections we recorded from 69 corticostriatal pairs of which 44 were connected in one direction and 25 reciprocally. Of these connections 41 were corticostriatal (9 inhibitory) and 53 striatocortical (all inhibitory). The observed excitatory responses were of variable amplitude (-10 to -370 pA, n=32). We found the connections very secure – with negligible failures on repeated (approx. 1Hz) stimulation of the cortical neuron. Inhibitory corticostriatal responses were also observed (-13 to -314pA, n=9). Possibly due to the mixed type of culture we found an inhibitory striatocortical response (-14 to -598pA, n=53). We are now recording from neurons in separate compartments to more closely emulate neuroanatomical conditions but still with the possibility of the easier identification of the connectivity.